2013
DOI: 10.1093/nar/gkt997
|View full text |Cite
|
Sign up to set email alerts
|

JASPAR 2014: an extensively expanded and updated open-access database of transcription factor binding profiles

Abstract: JASPAR (http://jaspar.genereg.net) is the largest open-access database of matrix-based nucleotide profiles describing the binding preference of transcription factors from multiple species. The fifth major release greatly expands the heart of JASPAR—the JASPAR CORE subcollection, which contains curated, non-redundant profiles—with 135 new curated profiles (74 in vertebrates, 8 in Drosophila melanogaster, 10 in Caenorhabditis elegans and 43 in Arabidopsis thaliana; a 30% increase in total) and 43 older updated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
890
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 932 publications
(906 citation statements)
references
References 32 publications
15
890
1
Order By: Relevance
“…As shown in Figure 1a, some of these binding sites were located at histone acetylated and DNAse-sensitive regions in the LAMP2 gene, both factors being typical of active enhancers. We then used a Python-based bioinformatics analysis to scan these binding regions for the consensus ARE as established in the JASPAR database [27]. We detected 8 putative AREs in the LAMP2 gene (Table S1) and 3 of them showed a relative score higher than 85%, a commonly used threshold for transcription factor binding-site analysis [28,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1a, some of these binding sites were located at histone acetylated and DNAse-sensitive regions in the LAMP2 gene, both factors being typical of active enhancers. We then used a Python-based bioinformatics analysis to scan these binding regions for the consensus ARE as established in the JASPAR database [27]. We detected 8 putative AREs in the LAMP2 gene (Table S1) and 3 of them showed a relative score higher than 85%, a commonly used threshold for transcription factor binding-site analysis [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The putative MAFK, MAFF and BACH1 binding regions were localized in 200–400 base-pair-long DNase-sensitive and H3K27Ac-rich regions. In addition, a frequency matrix of the consensus ARE sequence based on the JASPAR database [27] was converted to a position-specific scoring matrix and a script was generated with the Python 3.4 program to scan the promoter sequences with candidate AREs as previously described [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Importantly, our results show that DeepBind models trained in vitro work well at scoring in vivo data, suggesting an ability to capture genuine properties of nucleic acid binding Figure 6 Comparison of motifs learned by DeepBind with known motifs. Example motif detectors learned by DeepBind models, along with known motifs from CISBP-RNA 22 (for RBPs) and JASPAR 30 (for transcription factors). A protein's motifs can collectively suggest putative RNA-and DNA-binding properties, as outlined 51 , such as variable-width gaps (HNRNPA1, Tp53), position interdependence (CTCF, NR4A2), and secondary motifs (PTBP1, Sox10, Pou2f2).…”
Section: Discussionmentioning
confidence: 99%
“…3e and Supplementary Table 5). We additionally tested the DeepBind FoxA2 ChIP-seq model using 64 'electrophoretic mobility shift assay' (EMSA)-measured binding affinities 29 and found that it achieves the highest Spearman correlation among published methods, including JASPAR PWMs 30 , TRANSFAC PWMs 31 , and other models trained on ChIP-seq data (Supplementary Notes, sec. 6.3 and Supplementary Fig.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…Custom P erl scripts were used to scan the diatom NET alignment to identify conserved intergenic blocks (window, 20 bp; step, 10 bp) which do not overlap gene/expressed sequence tags in the species conserved. Searches for transcription factor binding sites were performed using J aspar 2014 (Mathelier et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%